Skip to main content

#F (x) = 3x + 5 # und #g (x) = -8x-10 #, wie finden Sie f (x) + g (x), f (x) -g (x), f ( x) * g (x), #f (x) divg (x) #?

Antworten:

siehe unten....

Erläuterung:

#f (x) + g (x) = 3x + 5-8x-10 #

#f (x) + g (x) = - 5x-7 #

#-------------------#

#f (x) -g (x) = 3x + 5 - (- 8x-10) #

#f (x) -g (x) = 3x + 5 + 8x + 10 #

#f (x) -g (x) = 11x + 15 #

#-------------------#

#f (x) * g (x) = (3x + 5) (- 8x-10) #

#f (x) * g (x) = - 24x ^ 2-70x-50 #

#-------------------#

#f (x) / g (x) = (3x + 5) / (- 8x-10) #

#f (x) / g (x) = - (3x + 5) / (2 (4x + 5)) #